2021
DOI: 10.1155/2021/6612776
|View full text |Cite|
|
Sign up to set email alerts
|

A Systematic Review of Lymphangioleiomyomatosis on Diagnosis and Molecular Mechanism

Abstract: Objective. Lymphangioleiomyomatosis (LAM) is a rare low-grade metastatic tumor; however, LAM patients were always found in young age with difficulty for diagnosis. Our study is aimed at observing the clinical characteristics of patients with lymphangiomatosis, including the clinical manifestations, imaging findings, histopathological features, and immunophenotype. Methods. We did a systematic review on LAM/PLAM cases, especially on male cases, and collected the clinical features and molecular mechanisms of PLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%